2005
DOI: 10.1002/mus.20403
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function tests and blood gases in worsening myasthenia gravis

Abstract: The aim of this study was to determine whether pulmonary function tests have a role in predicting the need for ventilation support in myasthenia gravis. Medical records were reviewed for 42 patients with severe myasthenia gravis who required 55 admissions to the intensive care unit. Patients with a vital capacity of more than 20 ml/kg, a maximal expiratory pressure more than 40 cm H(2)O, or a maximal inspiratory pressure more negative than -40 cm H(2)O are unlikely to require mechanical ventilation. A decline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Most studies to date carried out pulmonary function examinations either in isolated ocular or moderately to severely affected generalized MG patients (7,8,(14)(15)(16). Most studies to date carried out pulmonary function examinations either in isolated ocular or moderately to severely affected generalized MG patients (7,8,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies to date carried out pulmonary function examinations either in isolated ocular or moderately to severely affected generalized MG patients (7,8,(14)(15)(16). Most studies to date carried out pulmonary function examinations either in isolated ocular or moderately to severely affected generalized MG patients (7,8,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Lung function testing is an objective means to verify ventilatory dysfunction (7,8). A cardiopulmonary exercise test is usually used to differentiate between cardiovascular and pulmonary causes of Objectives -Myasthenia gravis (MG) is an autoimmune disease of neuromuscular synapses, characterized by muscular weakness and reduced endurance.…”
Section: Introductionmentioning
confidence: 99%
“…The unpredictable nature of these patients' respiratory status and poorly predictive values of their initial pulmonary function tests [7] make it difficult to decide between unnecessary intubation and iatrogenic harm and intubation prior to respiratory exhaustion. In adults, many studies have shown NIV to play a role in helping to prevent intubation [810].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis of myasthenia gravis was confirmed by a strongly positive acetylcholine receptor antibody results (136×1010 M). CT chest showed a thymoma.…”
Section: Myasthenia Gravismentioning
confidence: 92%
“…As ventilation decreases below 4–6 l/min, PaCO 2 rises precipitously (figure 3). 9 The degree of hypoxemia and hypercapnia varies according to the severity of the neuromuscular weakness 10…”
Section: Myasthenia Gravismentioning
confidence: 99%